Пам'яті майстра гончарного мистецтва (До 85-річчя від дня народження заслуженого майстра народної творчості О. Луцишина) - Лисюк, О. (Народна творчість та етнографія, 2007)
The article is the excursion into the life history of famous potter Oleksiy Lutsyshyn. This article describes his hard creative career from the life in Kryzhintsi, his native village which is situated in Vinnytska oblast, to his work abroad. The crown of his work became opening of Oleksiy Lutsyshyn Museum of Fictile Art in Vinnytsya.